REMARKS ON THE AGE OF THE LIMESTONES OF SOUTHEASTERN JAVA (INDONESIA) (Rivista italiana di Paleontologia e Stratigrafia, 1991)
The present paper deals with the age assignment of the limestones (Wonosari Formation) cropping out in the East Southern Mountains of South East Java (Indonesia), based on the foraminiferal assemblages observed in several limestone samples from that area. The assemblages are typical of Lower Tf stage; ages range from planktonic foraminiferal Zone N8 toZone N9 or are slightly younger, corresponding to Langhian and earliest Serravallian in terms of Mediterranean stages. The limestones with Flosculinella bontangensis of the East Southern Mountains of Java, have the same age of those of the Australian margin. They correlate with Zone N9 or with a stratigraphic interval ranging from Zone N9 to basal N10.